2016
DOI: 10.1097/md.0000000000003881
|View full text |Cite|
|
Sign up to set email alerts
|

Social support and the self-rated health of older people

Abstract: The lack of social support in elderly populations incurs real societal costs and can lead to their poor health. The aim of this study is to investigate the self-rated health (SRH) and social support among older people as well as its associated factors.We conducted a cross-sectional study among 312 urban community-dwelling elderly aged 65 to 90 years in Tainan Taiwan and Fuzhou Fujian Province from March 2012 to October 2012. A Spearson correlation test, independent t test, a Pearson χ2 test, a linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 91 publications
6
39
0
3
Order By: Relevance
“…This finding is supported by Dai et al, [6] who identified that few demographic characteristics as age, marital status, and education were generally related to the received social support. In addition, living together with older patient who visited ED was associated with another subarea of social support.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This finding is supported by Dai et al, [6] who identified that few demographic characteristics as age, marital status, and education were generally related to the received social support. In addition, living together with older patient who visited ED was associated with another subarea of social support.…”
Section: Discussionsupporting
confidence: 80%
“…[14] This may lead to an increase in health care utilization and related costs. Frequent use of health care services is one reason older patients apply for social support, [4][5][6] and should be considered when providing ED care for this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of previous papers regarding depressive symptoms was difficult using SRH-age and not SRH-global [26, 27]. As we performed the same methods as those used in the previous studies using SRH-global and SRH-age alone, the results from both health status variables showed similar trends to the CESD.…”
Section: Discussionmentioning
confidence: 87%